Grounded Histories of British Antislavery in Sierra Leone - den Otter, Sandra (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
Padriac Scanlan’s Freedom’s Debtors: British Antislavery in Sierra Leone in the Age of Revolution (2017) provides an opportunity to examine the early decades of antislavery from the vantage point of the western coast of Africa and to challenge triumphalist narratives of abolition.  The history of Sierra Leone demonstrates that intertwined with the rhetoric of liberty and uplift in the abolition of slavery was a unflinching determination to generate profit and commercial opportunity.  Metropolitan and colonial elites continued to profit from slavery long after its abolition.  A grounded history of ideas, both of humanitarian and legal ideas, is a valuable methodology to explore the history of antislavery. The inchoate, fluid and disordered attempts to put antislavery into practice at a very local level point to the fits and starts, continuities and discontinuities, and haphazard interventions in the making of a vernacular ideology of the antislavery and the civilizing mission.